1998
DOI: 10.1590/s0104-11691998000400004
|View full text |Cite
|
Sign up to set email alerts
|

Influência de fatores anátomo-fisiológicos na medida indireta da pressão arterial: identificação do conhecimento dos enfermeiros

Abstract: INTRODUÇÃOA continuidade da vida ocorre graças à manutenção do aporte de oxigênio necessário aos tecidos e à remoção dos produtos catabólicos, o que é garantido pela preservação das condições hemodinâmicas. A pressão arterial (PA), produto do débito cardíaco e da resistência dos vasos periféricos, é elemento fundamental da dinâmica sangüínea e para garantir a nutrição tecidual é necessário que a tensão na parede arterial atinja determinados níveis. Assim, a PA é um dos mais importantes parâmetros de avaliação … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
0
3
0
6
Order By: Relevance
“…F, the patient should be relaxed with his/her back supported on the back of the chair. 6 It is evident, therefore, that the patient's position and the arm supported at the height of the heart with the palm facing upwards are indispensable for a good evaluation of BP by indirect measurement. Thus, it is clear that the approach used for this issue needs to be modified so that more reliable indirect BP measurements can be obtained in the future.…”
Section: Discussionmentioning
confidence: 99%
“…F, the patient should be relaxed with his/her back supported on the back of the chair. 6 It is evident, therefore, that the patient's position and the arm supported at the height of the heart with the palm facing upwards are indispensable for a good evaluation of BP by indirect measurement. Thus, it is clear that the approach used for this issue needs to be modified so that more reliable indirect BP measurements can be obtained in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed at assessing the way blood pressure was measured by different health professionals at a hospital, considering the steps reported in the literature and defined in the methodology of this study. Several researchers have tried to identify whether the health professionals have been performing this procedure adequately, because it is directly related to the evaluation of a vital parameter 3,[13][14][15][16] . In the assisting practice among different professionals and at different places, blood pressure measurement is not correctly taken, which may compromise the values obtained, and, consequently, the diagnosis, treatment, and control of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In the assisting practice among different professionals and at different places, blood pressure measurement is not correctly taken, which may compromise the values obtained, and, consequently, the diagnosis, treatment, and control of hypertension. Recently, studies carried out in São Paulo 13,14 have reported that most nurses ignore the meaning of blood pressure measurements. Other studies have also shown irregularities in this procedure 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Os primeiros estudos científicos que avaliaram o efeito de intervenções educativas na melhora do conhecimento de profissionais de enfermagem sobre medida indireta da PA e registro de enfermagem foram publicados nos últimos dezoito anos (MOREIRA et al, 1999;CONSIDINE et al, 2006), muito embora pesquisas anteriores já tivessem encontrado lacunas no conhecimento teóricoprático desses profissionais (DE ARAUJO, 1994;ARCURI, 1998;GILLESPIE;CURZIO, 1998;LIMA et al, 2000;ARMSTRONG, 2002;RABELLO et al, 2004;CORDELLA et al, 2005).…”
Section: Discussionunclassified
“…A partir desta revisão, foram encontradas duas teses de doutorado (CLOUTIER, 2007;, quatro dissertações de mestrado (ALMEIDA, 2011; TOGNOLI, 2012; MOURO, 2014; NEVES, 2015) e 13 artigos científicos (NOLAN;NOLAN, 1993;ARCURI, 1998;GILLESPIE;CURZIO, 1998;LIMA et al, 2000;ARMSTRONG, 2002;RABELLO et al, 2004;CORDELLA et al, 2005;DICKSON;HAJJAR, 2007;GARCIA et al, 3. Ao verificar valores de pressão arterial com alterações significativas deve-se (assinale verdadeiro ou falso): a) Garantir que a medida da pressão arterial tenha sido realizada com técnica correta, caso contrário, uma nova medida deve ser feita.…”
Section: Validação De Aparência E Conteúdounclassified